2015
DOI: 10.3390/ijms17010014
|View full text |Cite
|
Sign up to set email alerts
|

RUCAM in Drug and Herb Induced Liver Injury: The Update

Abstract: RUCAM (Roussel Uclaf Causality Assessment Method) or its previous synonym CIOMS (Council for International Organizations of Medical Sciences) is a well established tool in common use to quantitatively assess causality in cases of suspected drug induced liver injury (DILI) and herb induced liver injury (HILI). Historical background and the original work confirm the use of RUCAM as single term for future cases, dismissing now the term CIOMS for reasons of simplicity and clarity. RUCAM represents a structured, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
840
0
34

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(987 citation statements)
references
References 155 publications
6
840
0
34
Order By: Relevance
“…The plants associated with hepatic signs and symptoms in this study Camellia sinensis (L.) Kuntze (Bunchorntavakul, 2013;Mazzanti, 2009), Dioscorea villosa L. (Wojcikowski, 2008), and Mentha piperita L. (Akdogan, 2004) exist, the design of the present study does not allow to add further evidence, particularly if the plant was part of a multi-ingredient product. In addition, a causality assessment according to RUCAM (Roussel Uclaf Causality Assessment Method), which is the reference method for evaluating drug and herb induced liver injury (Danan, 2016), was not possible due to incomplete case information. This is for example the case for Dioscorea villosa L., which was involved in two of the four cases of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plants associated with hepatic signs and symptoms in this study Camellia sinensis (L.) Kuntze (Bunchorntavakul, 2013;Mazzanti, 2009), Dioscorea villosa L. (Wojcikowski, 2008), and Mentha piperita L. (Akdogan, 2004) exist, the design of the present study does not allow to add further evidence, particularly if the plant was part of a multi-ingredient product. In addition, a causality assessment according to RUCAM (Roussel Uclaf Causality Assessment Method), which is the reference method for evaluating drug and herb induced liver injury (Danan, 2016), was not possible due to incomplete case information. This is for example the case for Dioscorea villosa L., which was involved in two of the four cases of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This is for example the case for the ingested dose of a PFS or a plant, which could not always be recorded or specified in detail. In addition, this is the reason why causality assessment of hepatotoxicity cases according to RUCAM (Danan, 2016) was not possible.…”
Section: Limitationsmentioning
confidence: 99%
“…Later during follow-up, laboratory investigations exhibited liver enzymes within the normal range. Furthermore, the causal relationship was established using Naranjo's algorithm (score -6) and Roussel Uclaf Causality Assessment Method (score -5), displayed a "probable" and "possible" association [21][22][23]. Furthermore, Hartwig's severity scale [24,25] and Thornton's preventability scale [26] demonstrated adverse drug reaction to being moderately severe and not preventable, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the toxicities associated with herbal TCM are well understood or documented: Wang et al (2015) have described an experiment that proved kudzu root extractinduced hepatotoxicity; an experiment in rats showed that yuanhuapine-induced intestinal and hepatic toxicities were correlated with disturbance of amino acid metabolism, lipid metabolism, carbohydrate metabolism, and gut microflora (Chen et al, 2015); and, from 1992 to 2015, 693 cases have been reported for Chinese herbal hepatotoxicity . Hepatotoxicity by herbal TCM must be validly established using a causality assessment method that is specific for the liver and hepatotoxicity such as Roussel Uclaf Causality Assessment Method (RUCAM) (Danan and Teschke, 2016).…”
Section: Hepatotoxicitymentioning
confidence: 99%